Taxonomic status of Engraulis nattereri Steindachner, 1880 (Osteichthyes: Clupeiformes: Engraulidae) - Loeb, Marina Vianna; Menezes, Naércio Aquino (Zootaxa, 2015)
Engraulis nattereri Steindachner, 1880 was described on the basis of five specimens collected in Pará during the Nathaniel Thayer Expedition. Later on, the species was assigned to Anchoviella by Fowler (1941). Including Anchoviella nattereri (Steindachner, 1880), Anchoviella comprises 17 small to medium-sized valid species (20–160 mm standard length), nine of them distributed in freshwaters of the Amazon, Essequibo, Corantijn and Orinoco river basins, and other eight brackish and marine species distributed along the Atlantic and Pacific coasts of North, Central and South America (Loeb & Figueiredo, 2014).